2015
DOI: 10.1007/s00415-015-7860-y
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular-evoked myogenic potentials in central vestibular disorders

Abstract: Vestibular-evoked myogenic potentials (VEMPs) are short latency manifestations of vestibuloocular and vestibulocollic reflexes that originate from the utricle and saccule. Although cervical and ocular VEMPs have mostly been applied to peripheral vestibular disorders, the characteristics and the diagnostic values of VEMPs have been expanded to assess the function of the central otolithic pathways. In the central nervous system, the cervical VEMPs (cVEMPs) are mediated by the vestibular nuclei and uncrossed medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 62 publications
(103 reference statements)
0
44
1
1
Order By: Relevance
“…Accumulating evidence shows that cVEMPs combined with oVEMPs can detect a significantly higher percentage of abnormalities in the central vestibular pathway, despite some research groups reporting inconsistent results. 6,22 An intriguing finding in our study was that the rate of oVEMP wave acquisition (96.4%) was higher than that of cVEMP (86.9%) in the control group. This finding is in contrast to a previous study that investigated the relationship between VEMPs and OSAS and showed that the rate of obtaining oVEMP waves was lower than that of cVEMP.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Accumulating evidence shows that cVEMPs combined with oVEMPs can detect a significantly higher percentage of abnormalities in the central vestibular pathway, despite some research groups reporting inconsistent results. 6,22 An intriguing finding in our study was that the rate of oVEMP wave acquisition (96.4%) was higher than that of cVEMP (86.9%) in the control group. This finding is in contrast to a previous study that investigated the relationship between VEMPs and OSAS and showed that the rate of obtaining oVEMP waves was lower than that of cVEMP.…”
Section: Discussionmentioning
confidence: 50%
“…oVEMP represents a crossed excitatory vestibulo-ocular reflex following activation of the utricular nerve that mainly passes through the medial longitudinal fasciculus from the upper brainstem to the midbrain. 6 Consequently, combined measurement of oVEMPs and cVEMPs should be a complementary approach for investigating clinically silent lesions in patients with OSAS. Accumulating evidence shows that cVEMPs combined with oVEMPs can detect a significantly higher percentage of abnormalities in the central vestibular pathway, despite some research groups reporting inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cervical and ocular VEMP tests are useful to assess the VOR and VCR pathways in MS patients. [16] In the cVEMP test, the same-side (non-crossed) medial vestibulospinal tract (extending to the spinal accessory core and vestibular nuclei) is evaluated. The oVEMP test explores the functions of the vestibular nuclei and VOR pathways via the contralateral…”
Section: Discussionmentioning
confidence: 99%
“…As the VCR and VOR arch pathways are located principally in the brainstem, the VEMP testing may yield information on brainstem lesions, although MRI shows no brainstem involvement. [6,[13][14][15][16] In the present study, we aimed to evaluate the role of cVEMP and oVEMP tests in the vestibular system in patients with relapsing-remitting MS (RRMS).…”
mentioning
confidence: 99%